Chelyabinsk Diocese Under Bishop Yuvenaly (Kilin). 1947–1948 - Tatiana A. Chumachenko; Pavel A. Efimushkin (Вестник Екатеринбургской духовной семинарии, 2023)
This article analyzes the processes of establishment and development of church and religious life in the newly formed Chelyabinsk eparchy under the guidance of Bishop Yuvenaly (Ivan Kelsievich Kilin), on the basis of archival documents including those introduced into the scientific discourse for the first time. The ministry of Bishop Yuvenaly in Harbin, as well as his years of governing the Irkutsk eparchy, are sufficiently covered in contemporary literature. However, the incomplete year of his administration of the Chelyabinsk diocese after his return from China has remained beyond the interest of ecclesiastical and secular researchers to this day. During the years of the Great Patriotic War, especially after the Kremlin meeting of Stalin with the three metropolitans of the Russian Orthodox Church in September 1943, the country witnessed an active revival of religious life. The traditional structure of church government was restoring, and new eparchies were forming, the publishing and educational activities of the Moscow Patriarchate were resumed and churches and houses of worship were open. In May 1947, by a special resolution of the Holy Synod, the parishes of the Chelyabinsk region were reorganized into a separate eparchy. Bishop Yuvenaly (Kilin), titled Bishop of Chelyabinsk and Zlatoust, was appointed its governor. It was the first eparchy under his administration after his reunion with the Moscow Patriarchate and his return from China topermanent residence in the Soviet Union. The article examines forms of the bishop’s management of the eparchy, and main directions of his ministry to revive the Church in the Chelyabinsk region in the postwar period. Particular attention is paid to the analysis of the relationship of the governing bishop with the Commissioner of the Council for the Affairs of the Russian Orthodox Church in the Chelyabinsk region, as well as with the Soviet authorities’ representatives of various levels and with the directors of large industrial enterprises. The conclusion is drawn that the short period of Bishop Yuvenaly’s administration became a year of flourishing church-religious life inthe Chelyabinsk region. During the entire history of Soviet regime, under Bishop Yuvenaly in the region there have been the largest number of Orthodox churches and houses of worship, the greatest number of Orthodox clergy, and a significant number of believers, the number of religious rituals has grown, as well as the income increase of the eparchy.